Effect of Embodied Argumentation with Hand Puppets in Fourth-Graders’ Mathematical Thinking - Roberto Araya; Carlos Aguirre; Mario Díaz (Interaction Design and Architecture(s))
Argumentation is one of the core skills in mathematics. However, it is challenging for fourth graders since explanations require complex thinking. To facilitate this process, we propose the “embodied argumentation” strategy. This involves using hand puppets as a scaffold to support the internalization of dialogs with third parties into inner speech dialogs. We performed an RCT with 20 low-income 4th-grade classes in two types of treatments and 117 classes as control. In 10 classes, students practiced constructing written arguments with puppets just before responding to open-ended math questions. In the other 10 classes, students used puppets long after answering. Using a machine learning-based classifier, we found a statistically significant effect size of 0.2 SD in response coherence for those who practiced with puppets just before answering. This suggests that embodied argumentation can effectively enhance argument clarity and reasoning in young students. Moreover, teachers reported applicability to other STEAM subjects.